The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1037/sgd0000482
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of online relationship seeking among transgender and gender diverse adolescents: Advice for others and common inquiries.

Abstract: Online relationship seeking is a normative aspect of adolescent development and is common among sexual minority adolescents. Yet, little is known about transgender and gender diverse (TGD) adolescents' subjective experiences with and needs related to online relationship seeking. This online, mixed-method study examined TGD adolescents' patterns and experiences of online relationship seeking. A sample of 130 TGD adolescents (68.5% non-Hispanic White, M age 16.8 years, 73.8% transgender men) were recruited onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
10
1
Order By: Relevance
“…We have focused here on how appearance-related SM behaviors may increase the risk for body image concerns, depressive symptoms, and disordered eating. However, other SM behaviors may promote positive mental health and well-being, such as those that promote identity exploration, creative expression, community building, and meaningful conversations with friends (e.g., Anderson & Jiang, 2018b ; Ma et al, 2021 ; Maheux et al, 2021 ; and see Hamilton et al, 2021 ). We recommend the following as preliminary guidelines for clinicians’ work with adolescent girls: (1) If the adolescent client is struggling with body image concerns, the clinician might assess whether she is engaging with SM in ways that may exacerbate these concerns, such as through upward social comparisons, editing selfies, or following beauty-oriented influencer content; (2) if yes, the clinician might try using techniques from evidence-based approaches to treating other problematic behaviors, such as motivational interviewing, urge-surfing, and cognitive restructuring approaches (e.g., Bowen & Marlatt, 2009 ; Harris et al, 2017 ; Naar-King, 2011 ; Sudhir, 2015 ), to encourage the client to spend more time on SM or offline activities that improve, rather than worsen, her body image and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…We have focused here on how appearance-related SM behaviors may increase the risk for body image concerns, depressive symptoms, and disordered eating. However, other SM behaviors may promote positive mental health and well-being, such as those that promote identity exploration, creative expression, community building, and meaningful conversations with friends (e.g., Anderson & Jiang, 2018b ; Ma et al, 2021 ; Maheux et al, 2021 ; and see Hamilton et al, 2021 ). We recommend the following as preliminary guidelines for clinicians’ work with adolescent girls: (1) If the adolescent client is struggling with body image concerns, the clinician might assess whether she is engaging with SM in ways that may exacerbate these concerns, such as through upward social comparisons, editing selfies, or following beauty-oriented influencer content; (2) if yes, the clinician might try using techniques from evidence-based approaches to treating other problematic behaviors, such as motivational interviewing, urge-surfing, and cognitive restructuring approaches (e.g., Bowen & Marlatt, 2009 ; Harris et al, 2017 ; Naar-King, 2011 ; Sudhir, 2015 ), to encourage the client to spend more time on SM or offline activities that improve, rather than worsen, her body image and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…peers) rather than from those perceived as inequivalent in status. Likewise, studies have also shown that individuals tend to seek advice from people who are more similar to them (prototypicality), such as the study by Ma et al (2021) on seeking online relationships among sexually minority adolescents. Characteristics of the advice-seeker is another factor whereby past research looking at demographic and sociocultural variables found that subgroups of society which were more dependent and vulnerable (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the exclusion of TGD adults from most previous research in the area, and the limited focus on them as victims rather than perpetrators [43], it was difficult to make predictions about the relative standing of TGD adults compared to cisgender adults in relation to perpetration behaviours. Our results clearly show that TGD adults were similar to ciswomen in terms of reporting lower levels of cyberbullyingperpetration than cismen, and were even lower even than ciswomen in relation to non-consensual sexting perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals can proactively declare their identity thereby signalling their availability to compatible others [21], and take advantage of geolocation features and dedicated online sites to find compatible others even when they are distributed over a large area [68][69][70]. Use of these strategies online can help to reduce the risk of rejection and hostility [31], help to reduce fear [42], and improve confidence and comfort [43] with seeking relationships online. Unfortunately, there is very little empirical research on online relationships TGD 1 3 adolescents or youths, and even less research into the attitudes and beliefs that influence relationship behaviours across different online contexts [13,69,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation